Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $(u_n)$ be a sequence defined by:

$$\begin{equation} \left\{ u_0 \geq 0 \\ \forall n \in \mathbb{N}^*, u_n = \sqrt{n+u_{n-1}} \right. \end{equation}$$

I'd like to prove that when $n \rightarrow +\infty$ :

$$u_n \sim \sqrt n$$

This would basically mean that : $$\lim_{n\rightarrow\infty}\frac{u_n}{\sqrt{n}} = 1$$ That's to say : $$\lim_{n\rightarrow\infty}\sqrt{\frac{n+u_{n-1}}{n}} = 1$$

Well, we can't replace $u_{n-1}$ and go on down to $u_0$... The result seems quite logic though I have no idea how I can really prove that.

share|improve this question
add comment

2 Answers

up vote 2 down vote accepted

From a previous question of yours, we have: $$ \forall n \in \mathbb{N} : u_n \leq n + \frac{u_0}{2^n} \tag{1} $$

Clearly, $u_{n-1} \ge 0$. Therefore: $$ \sqrt{n} \le \sqrt{n + u_{n-1}} = u_n $$

This gives us a lower bound for the limit we want to prove: $$ \frac{u_n}{\sqrt{n}} \ge 1 \Rightarrow \lim_{n \to \infty} \frac{u_n}{\sqrt{n}} \ge 1 $$

Using the definition of $u_n$ twice, we have: $$ u_n = \sqrt{n + u_{n-1}} = \sqrt{n + \sqrt{n - 1 + u_{n-2}}} $$

Using the inequality in (1): $$ u_n \le \sqrt{n + \sqrt{n - 1 + n - 2 + \frac{u_0}{2^{n-2}}}} $$

Hence: $$ \frac{u_n}{\sqrt{n}} \le \sqrt{1 + \sqrt{\frac{2}{n} - \frac{3}{n^2} + \frac{u_0}{n^2 2^{n-2}}}} $$

The RHS converges to $1$ as $n \to \infty$. This gives us the upper bound we seek. Therefore: $$ \lim_{n \to \infty} \frac{u_n}{\sqrt{n}} = 1 $$

share|improve this answer
add comment

Let $v_n = u_n/\sqrt{n}$. Then $$ v_n = \frac{\sqrt{n+u_{n-1}}}{\sqrt{n}} = \sqrt{1 + \frac{\sqrt{n-1}}{{n}} v_{n-1}}$$

Since $v_{n-1} \ge 0$ we get $v_n \ge 1$. Moreover, since $\sqrt{1+t} \le 1 + t/2$ for $t \ge 0$ we get $v_n \le 1 + \dfrac{\sqrt{n-1}}{2n} v_{n-1}$. For any $\epsilon > 0$, take $N$ large enough that $\sqrt{N-1}/(2N) < \epsilon$. Then for $n > N$ we have $v_n \le 1 + \epsilon v_{n-1}$, which implies $v_n \le \frac{1}{1-\epsilon} + C \epsilon^n$ for $n > N$ where $C$ is some constant, and in particular $\limsup_{n \to \infty} v_n \le 1/(1-\epsilon)$. This being the case for all $\epsilon > 0$, we conclude that $\lim_{n \to \infty} v_n = 1$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.